What forecasting the prevalence of inflammatory bowel disease may tell us about its evolution on a national scale. (June 2019) - Santiago, Mafalda; Magro, Fernando; Correia, Luís; Portela, Francisco; Ministro, Paula; Lago, Paula; Dias, Cláudia Camila
Inflammatory bowel disease (IBD) is increasingly prevalent within western societies. Its complex and chronic facets in addition to its increasing prevalence place a great economic burden on our healthcare systems. Our aim was to estimate the national prevalence of IBD through predictive models. We used prevalence data which spans the years 2003–2007 to estimate prevalence until 2030 by means of four forecasting methods. Prevalence rates are estimated to be 4–6-times higher in 2030 when compared with 2003 with an average annual percent change of 5%. IBD is poised to have a substantial impact on healthcare systems in the near future, given its rapidly increasing prevalence. Forecasting methods will allow for a proactive stance on the development of health policies that will be needed to provide high quality and cost-effective care to these patients, while ensuring the economic viability of healthcare systems.